Tren Parental Involvement pada School Readiness Anak Usia Dini: Analisis Bibliometrik Dari 2023 Hingga 2025 Menggunakan VOSViewer - Nabilah Muthmainnah; Yeni Rachmawati (CV. ITTC INDONESIA, 2025)
Monitoring scientific publication trends is crucial for understanding the development of research topics and identifying open areas for study. This study aims to analyze research trends on Parental Involvement in Early Childhood School Readiness during the 2023–2025 period. The method used is bibliometric analysis with data collected through Google Scholar-based Publish or Perish (PoP). A total of 132 articles were analyzed using VOSviewer through three visualization types: Network Visualization, Overlay Visualization, and Density Visualization to identify keyword linkage patterns, theme developments based on publication year, and the density of frequently studied topics. The results show that the number of publications peaked in 2023 and experienced a significant decline in 2024–2025, indicating a shift in research focus post-pandemic. The network analysis revealed 14 main clusters, with central themes such as parental involvement, school readiness skills, childhood education, parenting, early literacy, and the mediating role of the family environment. The overlay visualization shows that topics related to digital literacy, parent-child collaboration, and parental beliefs are the latest trends. Overall, this study provides a comprehensive overview of publication dynamics and identifies opportunities for further research in the development of evidence-based programs for early childhood education.